2014
DOI: 10.1063/1.4870081
|View full text |Cite
|
Sign up to set email alerts
|

Properties of gravitationally equilibrated Yukawa systems—A molecular dynamics study

Abstract: Using 2D Molecular Dynamics simulation, the equilibrium and dynamical properties of a gravitationally equilibrated Yukawa liquid are investigated. We observe that due to asymmetry introduced in one direction by gravity, several interesting features arise. For example, for a given value of coupling parameter Γ, screening parameter κ, and according to a chosen value of gravitational force g (say in y-direction), the system is seen to exhibit super-, sub- or normal diffusion. Interestingly, x-averaged density pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…In these simulations thus the contribution to dust pressure from mean ES fields can not be exemplified. It should be noted that quadratic scaling of dust pressure has been observed earlier in other simulations 21,22 and experiments 23 . We defer further discussion on this issue to the last section.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…In these simulations thus the contribution to dust pressure from mean ES fields can not be exemplified. It should be noted that quadratic scaling of dust pressure has been observed earlier in other simulations 21,22 and experiments 23 . We defer further discussion on this issue to the last section.…”
Section: Introductionsupporting
confidence: 71%
“…It should also be noted that there is evidence that even though the scaling P d ∝ n 2 d has been derived with the assumption of weak coupling, it may be very robust; it is found to be valid deep in the strongly coupled regime. For example, in simulations of Charan et al dusty plasma is confined by external gravity 21 . The result of this simulation show P d ∝ n 2 d scaling in the bottom region where dust particles are compressed and strongly coupled.…”
Section: Discussionmentioning
confidence: 99%
“…Similar quadratic scaling of dust pressure is also observed in experiments on shock formation in a flowing 2D dusty plasma where Saitou et al have shown [42] that the condition of shock formation is satisfied by equation of state P d ∝ n γ d where γ ≃ 2.2. Some other examples where quadratic scaling is found to be valid in the even in the presence of correlations includes the simulations of Charan et al where P d ∝ n 2 d scaling is seen in the regions where dust particles are compressed by external gravity and dust is strongly coupled [43]. The simulation of Djouder et al for dust monolayer confined by parabolic potential shows that the equation of state near zero dust temperature follows the relation P d ∝ n 2∼2.165 d for a wide range of densities near the dust crystal [44].…”
Section: Discussionmentioning
confidence: 99%
“…This important paradigm of gravitationally equilibrated strongly coupled medium, found in both astrophysical as well as in laboratory conditions, and study of its equilibrium and dynamical properties is the focus of the present work. A part of this result has been published recently in Charan et al (2014).…”
Section: Introductionmentioning
confidence: 85%
“…For low grain densities, if all the dust grains are of the same size (and hence acquire the same charge) and same mass, then all the dust grains experience the same repulsive force (due to the sheath) act upwards and gravitational force act downwards. In this way, for all the particles the repulsive force and downward gravitational forces cancel at some height and a 2D-layer of grains, perpendicular to the direction of gravitational force is formed resulting in a 2D-bed of dust grains (Chu and I 1994;Pieper et al 1996). In a similar way, if there is size distribution of the dust grains (resulting in different charge on the grains) or mass distribution in dust grains then the Yukawa force and gravitational force balance at different heights in space and a 3D structure of dust grains is formed (Arp et al 2005).…”
Section: Introductionmentioning
confidence: 99%